Off‐fault long‐term damage: A condition to account for generic, triangular earthquake slip profiles. (29th April 2014) - Cappa, Frédéric; Perrin, Clément; Manighetti, Isabelle; Delor, Elodie
Abstract Natural earthquake slip profiles have a generic triangular shape which the available rupture dynamics models fail to reproduce. Long‐term faults are embedded in long‐damaged crustal material, and the properties of the long‐term damage vary both across and along the faults. We examine the effects of the predamaged state of the medium on the earthquake slip distributions. We simulate long‐term damage by the decrease in the elastic modulus of the medium around the fault. We model the dynamic crack‐like rupture of a slip‐weakening planar, right‐lateral strike‐slip fault, and search which geometries and elastic properties of the long‐term damage produce a triangular slip profile on the rupture. We find that such a profile is produced only when a laterally heterogeneous preexisting damage zone surrounds the ruptured fault. The highest on‐fault slip develops in the most compliant region of the damage zone, and not necessarily above the earthquake hypocenter. The coseismic slip decreases in zones of stiffer damage. The amount of coseismic slip dissipated in the damage zone is large, at least 25–40% of maximum on‐fault slip, and can occur over large distances from the fault. Our study thus emphasizes that off‐fault preexisting damage should be considered for an accurate description of earthquake ruptures. It also motivates a reformulation of the available earthquake source inversion models since most of them do not include the inelastic deformations that occur in the near field of the earthquake ruptures.